Comprehensive genomic and transcriptomic profiling of pulmonary nodules in synchronous multiple primary lung cancer - Xingsheng Liu; Kun Qian; Lei Su; Xiaoru Tian; Xin Zhao; Tengteng Wang; Li Han; Zhenzhen Li; Peilong Zhang; Ruotian Wang; Baodong Liu; Yuanbo Li; et al. (European Journal of Medical Research)
Abstract Background Synchronous multiple primary lung cancer (sMPLC) exhibits distinct histopathological characteristics among pulmonary nodules. However, a comprehensive understanding of the somatic mutation landscape and transcriptome heterogeneity is lacking. Therefore, our study aims to meticulously investigate genomic distinctions among multiple pulmonary nodules within individual patients. Methods We performed targeted DNA sequencing on tumor specimens and conducted bulk RNA transcriptome analysis on 53 multiple nodules originating from 26 lung cancer patients. The multiple nodules from the same patient was determined as major nodule and minor nodule. Additionally, the tumor tissues underwent histopathological evaluation through H&E staining, complemented by a comprehensive series of immunohistochemistry (IHC) analyses to detect protein expression. The detected protein markers encompassed PD-L1, Ki67, and others. Results For the 53 nodule samples from 26 MPLCs patients, EGFR was the mostly mutated genes, and the TP53 mutation frequency was notably different between major and minor nodules. Furthermore, pathway enrichment analysis based on the differentially expressed genes (DEGs) between major and minor nodules revealed the significantly active cell cycle and p53 pathways in the major nodules. Additionally, both major and minor nodules demonstrated mostly similar immune microenvironment and PD-L1 protein expression, and a significantly higher expression of Ki67. A noteworthy suppression was observed in the immune microenvironment in nodules, revealed by the expression of macrophage, neutrophils, and NK cells. Furthermore, minor nodules exhibited a modestly elevated expression of macrophages compared to major nodules. Additionally, among the significantly up-regulated cell cycle-related genes in the major nodules when compared with minor nodules, CCNE1 mRNA expression demonstrated significant correlation with poor prognosis in the lung cancer. Furthermore, the MYC inhibitor demonstrated more sensitivity for the major nodules than minor nodules. Conclusions This study validated molecular distinctions between samples from major and minor nodules in patients with sMPLC at both genomic and transcriptomic levels. The major nodules exhibited heightened activity in tumor cell proliferation pathways and demonstrated malignancy-related biological characteristics, which correlated with pathological assessment results.